Metode Unzur wa Qul dan Pengaruhnya Terhadap Pembelajaran Maharatul Qira’ah - Mohamad Rian Liputo; Ratni Bt. Hj. Bahri; Abdullah; Dzulkifli M Mooduto (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2024)
This research aims to determine the effect of the Unzur Wa Qul Method on the Maharah al-Qira'ah (reading skills) of Madrasah Tsanawiyah students. Using a quantitative approach with an experimental method and quasi-experimental design, this study was conducted on students in one of the Madrasah Tsanawiyah in Gorontalo City. The results show a significant influence of the Unzur Wa Qul Method on students' maharah al-qira'ah. Statistical analysis using SPSS 26.0 shows the Asymp. Sig. (2-Tailed) value for the experimental group is 0.000, which is less than 0.05. This indicates a significant difference between Pre-Test and Post-Test results in the experimental group. Furthermore, hypothesis testing confirms the positive and significant influence of the Unzur Wa Qul method, with an Asymp. Sig. (2-Tailed) value of 0.000, which is also less than 0.05. These findings affirm the effectiveness of the Unzur Wa Qul Method in improving students' Arabic reading skills. The implications of this research point to the potential for wider development and application of this method in Arabic language learning at the Madrasah Tsanawiyah level, particularly to enhance students' reading skills.